Penguatan Kapasitas SDM-ASN Berbasis Kinerja di BAPPEDA Kabupaten Banyuwangi - Rahman, Auliya Gaffar (Jurnal Ilmiah Administrasi Publik, 2021)
This research focuses on efforts to strengthen the capacity of the apparatus of human resources within the Bappeda office in the Banyuwangi Regency. One effort to improve the quality of the apparatus is the method of education and training (Diklat), salary systems, and working conditions. This study aims to determine the process of strengthening the capacity of the HR apparatus in the Bappeda environment and the factors that influence the strengthening of the HR capacity of the apparatus within the Bappeda environment. This study uses a qualitative method. In this research, the theory used is the theory of capacity development initiated by Grindle. The results of this study are that strengthening the capacity of human resources with the education and training methods carried out by Banyuwangi Bappeda has an impact on improving the performance of each apparatus in accordance with their main tasks and functions. The working conditions in the Bappeda of Banyuwangi Regency are classified as good, as can be seen from routine coaching between superiors and staff. The payroll system is in accordance with applicable regulations.